Rare germline mutation and MSH2-&MSH6 + expression in a double primary carcinoma of colorectal carcinoma and endometrial carcinoma: a case report - Tiansong Zhang; Xiaoqiang Huang; Wenjie Liu; Xiulan Ling; Zhenping Su; Mengwei Huang; Shuanlong Che (BMC, 2024)
Abstract Background Multiple primary malignancies are rare in cancer patients, and risk factors may include genetics, viral infection, smoking, radiation, and other environmental factors. Lynch syndrome (LS) is the most prevalent form of hereditary predisposition to double primary colorectal and endometrial cancer in females. LS, also known as hereditary nonpolyposis colorectal cancer (HNPCC), is a common autosomal dominant condition. Pathogenic germline variants in the DNA mismatch repair (MMR) genes, namely MLH1, MSH2, MSH6, and PMS2, and less frequently, deletions in the 3' end of EPCAM cause LS. It manifested itself as loss of MMR nuclear tumor staining (MMR protein deficient, dMMR). Case presentation This case study describes a double primary carcinoma in a 49-year-old female. In June 2022, the patient was diagnosed with highly to moderately differentiated endometrioid adenocarcinoma. The patient's mother died of esophageal cancer at age 50, and the father died of undefined reasons at age 70. Immunohistochemical stainings found ER (++), PR (++), P53 (+), MSH2 (-), MSH6 (+), MLH1 (+), and PMS2 (+). MMR gene sequencing was performed on endometrial tumor and peripheral blood samples from this patient. The patient carried two pathogenic somatic mutations in the endometrial tumor, MSH6 c.3261dupC (p.Phe1088LeufsTer5) and MSH2 c.445_448dup (p.Val150fs), in addition to a rare germline mutation MSH6 c.133G > C (p.Gly45Arg). Two years ago, the patient was diagnosed with moderately differentiated adenocarcinoma in the left-half colon. Immunohistochemical stainings found MSH2(-), MSH6(+), MLH1(+), and PMS2(+) (data not shown). Conclusions In the case of a patient with double primary EC and CRC, a careful evaluation of the IHC and the genetic data was presented. The patient carried rare compound heterozygous variants, a germline missense mutation, and a somatic frameshift mutation of MSH6, combined with a novel somatic null variant of MSH2. Our study broadened the variant spectrum of double primary cancer and provided insight into the molecular basis for abnormal MSH2 protein loss and double primary carcinoma.